VIII International Congress on Cognitive Linguistics «Cognitio and Communicatio in the Modern Global World» (Moscow State University of M.V. Lomonosov, Moscow, October 10–12, 2018) (Proceedings of Southern Federal University. Philology, 2019)
CHRONICLES